Study on the Microstructure and Electrical Properties of Boron and Sulfur Codoped Diamond Films Deposited Using Chemical Vapor Deposition. (21st May 2014) - Jing, Zhang; Rongbin, Li; Xianghu, Wang; Xicheng, Wei
Abstract : The atomic-scale microstructure and electron emission properties of boron and sulfur (denoted as B-S) codoped diamond films grown on high-temperature and high-pressure (HTHP) diamond and Si substrates were investigated using atom force microscopy (AFM), scanning tunneling microscopy (STM), secondary ion mass spectroscopy (SIMS), and current imaging tunneling spectroscopy (CITS) measurement techniques. The films grown on Si consisted of large grains with secondary nucleation, whereas those on HTHP diamond are composed of well-developed polycrystalline facets with an average size of 10–50 nm. SIMS analyses confirmed that sulfur was successfully introduced into diamond films, and a small amount of boron facilitated sulfur incorporation into diamond. Large tunneling currents were observed at some grain boundaries, and the emission character was better at the grain boundaries than that at the center of the crystal. The films grown on HTHP diamond substrates were much more perfect with higher quality than the films deposited on Si substrates. The local I-V characteristics for films deposited on Si or HTHP diamond substrates indicate n-type conduction.